A comparative cross-sectional study on early childhood development through anthropometric measurements among urban and rural Anganwadi children. - Nirvignyasree, Amancha; Shaikh, Fawwad M; Rao, Bollampalli Babu; N. Jayalatha (Student's Journal of Health Research Africa, 2025)
Background Early childhood is a crucial period for cognitive, physical, and emotional development. Nutritional status during this phase plays a significant role in shaping a child’s growth and development. Objectives To assess early childhood development through anthropometric measurements among Anganwadi children in urban and rural areas, and to compare the nutritional status between the two groups. Methods A comparative cross-sectional study was conducted from 25th November 2023 to 25th January 2024 among 254 children under five years attending Anganwadi centres, 129 from rural areas and 125 from urban areas. Anthropometric parameters such as weight, height, Body Mass Index (BMI), Mid-Upper Arm Circumference (MUAC), and head circumference were recorded. Developmental milestones were also assessed. The data were analysed using WHO growth standards, and Chi-square tests were applied for statistical significance. Results The study revealed that 77.5% of rural and 68.0% of urban children had normal weight-for-age, though the difference was not statistically significant (p = 0.233). Stunting was present in 37.2% of rural and 37.6% of urban children (p = 0.204). BMI analysis showed that 94.6% of rural and 87.2% of urban children were within the normal range (p = 0.118). Developmental delays were observed in 2.4% of rural and 8.0% of urban children. MUAC was normal in 99.2% of children across both groups (p = 0.982). No significant differences were found in head circumference (p = 0.926) or weight-for-height (p = 0.328) between the groups. Conclusion Children with lower anthropometric measurements were more likely to exhibit developmental delays. Rural Anganwadi children were relatively better nourished compared to urban children. Early detection of malnutrition through growth monitoring is vital for ensuring proper childhood development. Recommendations Regular anthropometric monitoring, nutrition education for caregivers, and strengthening Anganwadi services are essential to identify at-risk children early and implement timely interventions.